Studying Small Oscillations of Spin Vector of The Ferromagnetic With Spin S=1 (Latakia University Journal -Basic Sciences Series, 2019)
يهدف البحث إلى دراسة الأمواج السبينيّة في المغانط الحديدية ذات سبين  S=1 في جملة الإحداثيات المركبة, ويقسم البحث إلى ثلاثة محاور: يتلخّص  المحور الأول في إيجاد جملة نقل تمكننا من دراسة ظاهرة مجهريّة (ميكروسكوبيّة) , وهي الأمواج السبينيّة بطريقة كلاسيكية ، والخطوة الأولى تكمن في إيجاد التابع الموجي المناسب في الإحداثيات المختارة ثم الهاملتوني واللاغرانجي ثم المعادلات الديناميكية بالشكل العام, واختبار صحة تلك الجملة من خلال التأكد من أنها تحقق شروط المسألة . المحور الثاني هو استخدام تلك المنظومة (تسمّى الطريقة شبه الكلاسيكية) لدراسة الأمواج السبينيّة , واستنتاج علاقات التشتّت والسويّات الطاقيّة , ثم مناقشة تلك النتائج من مختلف الجوانب والتأثيرات. ويتضمّن المحور الثالث: 1-إيجاد السويّة الأساسية , نظراً لأنّ تحديدها يعطي فكرة عن طاقة الجملة. 2-إيجاد معادلات الحركة المرتبطة بالزمان والمكان(المعادلات الزمكانيّة) . وتكمن أهميتها في أنّها تمكّننا من جهة من معرفة تغيّر إحداثيات السبين بتابعية الزمن , ومن جهة أخرى معرفة سرعة انتشار الأمواج وفق المحور المختار, وارتباط تغيّر حدود القطاعات المغناطيسية بانتشار الأمواج السبينيّة وسرعتها. The aim of this paper is to study spin waves in ferromagnetic with spin (S=1/2) in complex coordinates system, the paper is divided into three sections: The First section is about finding a transportation system that enables us to study a microscopic phenomenon ,its the spin waves in a classical way. The first step in this transportation system lies in finding the suitable wave function in the chosen coordinates, then the Hamiltonian and the Lagrangian then after that the dynamic equations in the general form, and testing the credibility of the system by making sure that it follow the rules of the study. The Second section is about the use of that system, which is called the Simi classic way of studying the spin waves, and finding the dispersing equations and energetic levels then discussing the resultes from different ways and effects. The Third section includes 1- Finding the ground state (basic) and the importance of finding the energy of the ground state lies in its direct effect on the system's energy.2- Finding the movement equations connected with time and place (the time-place equations). Its importance lies in two points; the first one is that it enables us to find the variance in the coordinates of the spin according to time. The second point is to know the spread speed of spin waves according to the chosen axle and the connection of the variation of domains (the magnetic sectors) with the spreading of spin waves and its speed.